Leveraging intellectual capital through Lewin's Force Field Analysis: The case of software development companies - Alexandru Capatina; Gianita Bleoju; Florinda Matos; Valter Vairinhos (Journal of Innovation & Knowledge (JIK), 2017)
This article presents an original conceptual framework for the strategic management of intellectual capital assets in software development companies. The framework is based on Lewin's Force Field Analysis. The framework makes it possible to assess software company managers' opinions regarding the way driving and restraining forces affect the pillars of intellectual capital. The capacity to adapt to change is vital for companies in knowledge-intensive industries. Accordingly, this study examined a sample of 74 Romanian software development companies. The aim was to help companies benefit from managing the driving and restraining forces acting upon the pillars of intellectual capital (human, structural, and relational). The effects of the driving forces, quantified by PathMaker software's Force Field Tool, were observed to be greater than the restraining forces for each pillar of intellectual capital. This paper contributes by showing the explanatory power of this framework. The framework thus offers a tool that helps managers drive change in their organizations through effective intellectual capital management. Furthermore, this article describes how to encourage the implementation of changes that create value for software development companies.
Keywords: 650; Intellectual capital; Kurt Lewin; Force Field Analysis; Organizational change; Strategic intelligence; Software industry; Multidimensional scaling